Association of psychological, cognitive, and functional variables with self-reported executive functioning in a sample of nondemented community-dwelling older adults. Issue 4 (4th July 2017) - Meltzer, Erica P.; Kapoor, Ashu; Fogel, Joshua; Elbulok-Charcape, Milushka M.; Roth, Robert M.; Katz, Mindy J.; Lipton, Richard B.; Rabin, Laura A.
ABSTRACT: Subjective executive functioning (EF) measures provide valuable information about real-world difficulties, although it is unclear what variables actually associate with subjective EF scores. We investigated subjective EF in 245 nondemented, community-dwelling older adults (aged 70 and above) from the Einstein Aging Study. Partial correlational analyses controlling for age were performed between the nine Behavior Rating Inventory of Executive Function—Adult version (BRIEF-A) clinical scales and objective EF tests, self-reported mood and personality, and informant-reported activities of daily living. The significance level was set at p  < .006 for all analyses (two-tailed). Most notably, higher worry/oversensitivity, physiological anxiety, and fear of aging were significantly associated with increased EF difficulties on all nine BRIEF-A scales. Additionally, increased EF difficulties on five or more BRIEF-A scales were significantly associated with lower conscientiousness, higher neuroticism, and higher depressive symptom scores. The only objective neuropsychological test that significantly correlated with increased EF difficulties (on four BRIEF-A scales) was a measure of practical judgment. Overall, results indicate that interpretation of subjective EF scores must account for self-report of mood and personality. Moreover, the BRIEF-A only minimally taps objective EF as measured by performance-based measures. We discuss the theoretical and practical implications of these findings.